CATECHOLAMINE REQUESTS IN MALAYSIA: HOSPITAL KUALA LUMPUR'S EXPERIENCE - CR, Nur Shafini; Z, Nurharniza (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION The Chemical Pathology Unit in Hospital Kuala Lumpur is one of the centres that offer 24-hour urinary catecholamines in Malaysia. Urinary catecholamine determination is a specialised and expensive test offered in limited centres in Malaysia. It is important to reduce inappropriate requests as they can make up a large proportion of laboratory workload leading to unnecessarily increased cost. We review the clinical indications and the significance of results obtained for each catecholamine request sent to our laboratory. METHODOLOGY This is a retrospective study involving all requests for 24-hour urinary catecholamine tests sent from all over Malaysia that were available from 2014 until 2016. Clinical indications for requesting the test were reviewed based on information provided in the request forms. Catecholamine results were gathered from the laboratory information system. Clinical indications were classified into 5 categories. Results were tabulated into 3 groups: normal, borderline and abnormal. RESULTS A total of 3,151 requests and results were reviewed. The main indication for the test was for hypertension workup (85%), followed by nonspecific indications (9.4%), adrenal mass work-up (4%), neuroblastoma (1%) and MEN syndromes (0.1%). Out of 3,151 results, 0.5% were reported as abnormal (with significant elevation in any catecholamine metabolites) and 8% borderline (with nonsignificant elevation). For screening of secondary causes of hypertension, only 0.3% was found to have abnormal results. Some interventions taken by the laboratory to improve laboratory test utilisation include continuous feedback to clinicians for nonspecific indications, and revision of laboratory policy which allows only specialists to order the test. CONCLUSION In our institution, only 0.5% of the urinary catecholamine results were reported abnormal, consistent with the rare nature of the related diseases. The very low percentage of abnormal results for screening of secondary causes of hypertension may indicate the need to review the test ordering practices among clinicians.